INTERNAL CAROTID ARTERY DISSECTION AND DELAYED STROKE FOLLOWING RUGBY TACKLE – A CASE REPORT. Issue 22 (1st November 2016) - Cowlin, D; Dickinson, M; Sultan, S
Abstract : Following England's grand slam success in the 'Six Nations' tournament in 2016, publicity around the safety of rugby football is likely to be greater than ever before. Recent media coverage around players that have sustained head injuries in the context of competitive sporting events has also served to increase the awareness amongst sporting management, players and governing bodies alike. Significant head and neck injuries are thankfully rare in all contact sports. However there is always an element of risk when tough physical contact occurs between participants (either intentionally or accidental). The possible consequences of impact injuries, whilst occasional, should not be viewed as an unfortunate exception to the rule but should be used to increase and develop injury/clinical management/training strategies for all sporting levels, not just at the international end of the game. Sporting governing bodies such as the RFU (Rugby football Union) do much to minimise risk, including raising awareness of the consequence of head injuries and secondary impact syndrome, use of concussion scoring tools and removal of players from the field for formal assessment. However, these strategies are usually only utilised when players have sustained a head injury. This case study details a 36 year old male who collapsed 4 hours after competing in a rugby match. After initial diagnostic confusion, it later transpired he had suffered a middle cerebral artery thrombus, secondary to internal carotid artery dissection. This was as a consequence of a collision during a rugby match, and a suspected shearing or deceleration injury due to neck twisting during a tackle. This report will offer a unique and interesting insight into the patient's perspective of this injury – both at the time the actual stroke occurred and his subsequent rehabilitation journey. It will also discuss that whilst much publicity and training is offered around the assessment and management of head injuries and/or concussion, the possible intracerebral consequence of neck trauma sustained in contact sports seems to be less well publicised. This mechanism of injury should be considered in the emergency department as in this case the 'typical clinical presentation' of an extradural haematoma turned out to be something quite different.